2020
DOI: 10.1136/bmjopen-2020-038511
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression symptoms and its influencing factors among pregnant women in late pregnancy in urban areas of Hengyang City, Hunan Province, China: a cross-sectional study

Abstract: ObjectivesTo evaluate the prevalence of depressive symptoms and its influencing factors in late pregnancy.DesignCross-sectional study.SettingFourteen community in urban areas of Hengyang City.ParticipantsThe study conducted from July to October 2019, and surveyed 813 women in late pregnancy who lived in urban areas of Hengyang for more than 6 months, signed an informed consent and were without cognitive disorders, severe mental illnesses or other serious diseases.MeasuresPerinatal depression symptoms were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 34 publications
5
40
0
1
Order By: Relevance
“…The determinants of poor sleep quality among pregnant women were socio-economic status, age, divorce, body mass index, first pregnancy, history of fetal death, history of prolonged labor, zinc and fluorine deficiency, gestational period, and having a history of chronic medical illness (DM, hypertension), lack of awareness about sleep hygiene practice, unwanted pregnancy, lack of social support, and history of mental illness [ 2 , 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The determinants of poor sleep quality among pregnant women were socio-economic status, age, divorce, body mass index, first pregnancy, history of fetal death, history of prolonged labor, zinc and fluorine deficiency, gestational period, and having a history of chronic medical illness (DM, hypertension), lack of awareness about sleep hygiene practice, unwanted pregnancy, lack of social support, and history of mental illness [ 2 , 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our investigation reveals that the occurrence of prenatal depression is as high as 73.01% during the pandemic timeframe, which is a lot higher than that during the non-plague state 22,23 . This might be identified with the eruption of the pandemic and the exceptional time of pregnancy 24 .…”
Section: Discussionmentioning
confidence: 66%
“…These results are consistent with previous studies in China. Yu et al reported that the rate of depressive symptoms among pregnant women in late pregnancy in Hengyang City was 9.2% (95% CI, 7.2–11.2%) ( 36 ). Zhou et al showed that the detection rate of anxiety among pregnant women in Beijing was 6.8% during the COVID-19 epidemic ( 37 ).…”
Section: Discussionmentioning
confidence: 99%